DESARROLLO DE UN SISTEMA PORTÁTIL DE ANÁLISIS DE CALIDAD DE AGUA - Comina, Germán (2009)
A prototype has been developed that could monitor the water quality in real time based on an “electronic tongue”. The system is based on electrochemical methods and involves the combination of non-selective sensors (metal electrodes), the signal processing part, and a pattern recognition. It determines attributes (quality, status of a process, etc.) rather than single parameters. Unique response patterns for liquid samples are interpreted with principal components analysis. The prototype is portable and has evaluated the water quality in a rural area (Yaurisque, Cusco). The system could discriminate water with different chemical and bacterological composition.